Policy-Relevant Spatial Indicators of Urban Liveability And Sustainability: Scaling From Local to Global. Issue 4 (2nd October 2022) - Higgs, C.; Alderton, A.; Rozek, J.; Adlakha, D.; Badland, H.; Boeing, G.; Both, A.; Cerin, E.; Chandrabose, M.; De Gruyter, C.; De Livera, A.; Gunn, L.; et al.
ABSTRACT: Urban liveability is a global priority for creating healthy, sustainable cities. Measurement of policy-relevant spatial indicators of the built and natural environment supports city planning at all levels of government. Analysis of their spatial distribution within cities, and impacts on individuals and communities, is crucial to ensure planning decisions are effective and equitable. This paper outlines challenges and lessons from a 5-year collaborative research program, scaling up a software workflow for calculating a composite indicator of urban liveability for residential address points across Melbourne, to Australia's 21 largest cities, and further extension to 25 global cities in diverse contexts.